An Empirical Analysis of Mental Health and Social Support in the Elderly of Different Age Groups: A Survey and Analysis of Data from China - Huiyuan Qiang; Lin Liu (Occupational Therapy International)
To explore the effects of social support on the mental health of older adults in different age groups in China, and to provide reference for the development of social support policies to promote the mental health of older adults in China. This paper uses a random sampling method to conduct a questionnaire survey of 3,000 older adults aged 60 years or older in Nanjing and a dichotomous logistic regression model for empirical analysis. The two dimensions of mental health and social adjustment were used to measure the mental health status of the elderly. The results showed that the overall mental health status of the elderly in Nanjing city was more optimistic, and the nonempty nesters with male gender, higher education level, and partners were generally healthier; objective and subjective support had significant positive effects on the mental health of middle and high aged elderly, while the utilization of support had more significant effects on the health of low-aged elderly. This paper proposes that government departments should develop a localized elderly support system and social support policies adapted to the actual situation in Nanjing according to the quantitative distribution and demand characteristics of the mental health of elderly people in different age groups. The study is structured as follows: the second part contains data sources and statistical methods. The third part is the analysis of empirical results. The fourth part is the discussion and conclusion part of the article.